Harnessing intratumoral microbiota: new horizons in immune microenvironment and immunotherapy - Jinhe Zhang; Zinan You; Xinqiao Li; Jinpeng Hu; Jiamu Li; Zhitao Jing (Journal of Translational Medicine)
Abstract Microorganisms are ubiquitous in the human body, including within tumor tissues. Recent studies have demonstrated that intratumoral microbiota serve as critical regulators of the tumor microenvironment (TME), promoting the progression of solid tumors (e.g., gastric, lung, and breast cancers). These microbes modulate immune factors (such as IFN-γ and TNF-α), thereby influencing the activation and infiltration of immune cells, including T cells and macrophage. Additionally, by reshaping the immune landscape, intratumoral microbiota can dysregulate immune checkpoint expression, ultimately affecting the efficacy of cancer immunotherapy. This review synthesizes the current understanding of the origins of intratumoral microbiota, their heterogeneity across cancer types, and their intricate roles in modulating immune responses and tumor metastasis. We further discuss innovative therapeutic strategies leveraging the intratumoral microbiota, including engineered bacteria, oncolytic viruses, and nanoparticles, and address existing challenges and potential future research directions. A deeper understanding of these microbial‒host interactions may open new avenues for precise microbiota-based cancer diagnostics and personalized immunotherapeutic strategies.